ҒӘРЕЗСИЗЛИК ЖЫЛЛАРЫНДАҒЫ ҚАРАҚАЛПАҚ БАЛАЛАР ПОЭЗИЯСЫНДА АФОРИЗМЛЕРДИҢ ҚОЛЛАНЫЛЫЎ ӨЗГЕШЕЛИКЛЕРИ - Казахбаев, С.С. (FAN va JAMIYAT, 2016)
The article deals with the structure of poems and other kinds of Karakalpak poetry for children for the years of independence Aphorisms play a great role in children‘s poetry. The author studies the peculiarities of aphorisms and structure of poems by S.Abbasov, Kh. Saparov, T. Seytjanov, T.Kabulov. The complex size and structure of poems in Karakalpak poetry for children and their ideological-artistic and thematic features have also been investigated in the work.